Long‐Term post‐merger announcement performance. A case study of Australian listed real estate. (9th December 2015) - Ratcliffe, Chris; Dimovski, Bill; Keneley, Monica
Abstract: This study examines the long‐term postmerger performance of Australian Real Estate Investment Trusts (A‐REITs). The A‐REIT sector is used as a case study being less vulnerable to agency issues due to its regulatory structure (Eichholtz and Kok, 2008; Ratcliffe et al ., 2009). Research on conventional firms has shown, on average, shareholders are worse off in the long run (Alexandridis et al ., 2012). In contrast, we find that shareholders experience significantly positive abnormal returns, after accounting for the financial crisis. This outcome suggests that when managers are restricted with the use of retained earnings and the type of investment, they may be less susceptible to hubris and/or agency issues.